Program Sekolah Ramah Anak Dalam Pemenuhan Hak dan Perlindungan Khusus Anak di SD Negeri 064979: Sekolah Ramah Anak dan Pelaksanaannya - Sitorus, Alvida Hajni; Ginting, Bengkel (Medan Resource Center, 2023)
This research is motivated by a sense of concern about the world of education, which currently often occurs in various cases involving children. Based on data from the Indonesian Komisi Perlindungan Anak Indonesia (KPAI), there were 4,683 child case complaints throughout 2022, including 2,113 complaints related to special protection of children, 429 complaints related to the education and cultural sector, 41 complaints related to violations of children's freedom rights. This study used descriptive qualitative method. The subjects in this study were on the SRA SDN 064979 team, teachers and students with the research object including the implementation of the SRA program at SD Negeri 064979. Data collection techniques used interviews, observation and documentation. The results of the study show that bullying and violence are still common in children's play areas. Then, in its application it is necessary to pay attention to several SRA components, namely; SRA Policy; Trained educators and education personnel on children's rights; Implementation of a child-friendly learning process without violence; child-friendly facilities and infrastructure; Child participation, including: communicating school programs by involving children.